Soluble Insulin Receptor Levels in Plasma, Exosomes, and Urine and Its Association With HIV-Associated Neurocognitive Disorders - Cantres-Rosario, Yisel M.; Wojna, Valerie; Ruiz, Rafael; Diaz, Bexaida; Matos, Miriam; Rodriguez-Benitez, Rosa J.; Rodriguez, Elaine; Skolasky, Richard L.; Gerena, Yamil (Frontiers in Neurology, 2022)
Background HIV-associated neurocognitive disorders (HAND) are one of the HIV-associated comorbidities affecting 20–50% of the people with HIV (PWH) infection. We found that the soluble insulin receptor (sIR) levels in plasma and cerebrospinal fluid (CSF) were significantly higher in HIV-infected women. The mechanism of sIR release into the plasma remains unknown, but the detection of the sIR in exosomes may uncover novel mechanisms of sIR secretion from HIV-infected cells and its contribution to HIV disease progression and HAND development. Quantification of sIR in urine may represent a less invasive and more accessible diagnostic tool. Our objective was to quantify sIR levels in plasma, plasma-derived exosomes, and urine, and evaluate their association with HAND and renal function. Methods We measured full-length sIR in the plasma and urine of 38 controls and 76 HIV-infected women by ELISA, and sIR, HIV-1 Tat, and reactive oxygen species (ROS) in exosomes by flow cytometry. Results Plasma and exosomes with sIR were significantly higher in HIV-infected women when compared with controls and HAND. Exosomal sIR positively correlated with exosomal ROS and exosomal HIV-1 Tat in HIV-infected women. Exosomal ROS was significantly higher in HIV-infected women with more symptomatic cognitive impairment. Plasma-derived exosomes exhibited significantly higher levels of astrocyte (GFAP) and neuronal (L1CAM) markers in HIV-infected women, confirming the presence of circulating CNS-derived exosomes in the blood of HIV-infected women. Urine sIR positively correlated with eGFR in controls, but not in HIV-infected women, regardless there was no significant difference in renal function as determined by the estimated glomerular filtration rate (eGFR, p = 0.762). In HIV-infected women, higher plasma sIR correlated with lower urine sIR that could suggest sIR retention in blood or decreased renal filtration. Discussion Higher plasma sIR levels and their correlation with ROS in plasma-derived exosomes with HAND suggest a combined role of metabolic disturbances, oxidative stress, exosome release, and cognitive decline. Communication between CNS and periphery is compromised in PWH, thus plasma-derived exosomes may shed light on disrupted cellular mechanisms in the brain of PWH. High plasma and low urine sIR levels could suggest sIR retention in blood or decreased renal filtration.